Development of E-Module Using Team Assisted Individualization to Improve Higher Order Thinking Skills of High School Students in Fluid Physics - I Made Astra; Indriyani Nurjanah; Raihanati Raihanati (Science and Technology: Developments and Applications Vol. 5, 2025)
This study aims to develop independent teaching materials in the form of electronic modules (e-modules) that use the Team Assisted Individualization (TAI) cooperative model and include HOTS questions on fluid dynamics material. The method used in this study is research and development with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development stages. The TAI cooperative model has five stages of learning, namely teams, placement tests, team study, factual tests, and lastly team score and team recognition. The developed e-module also included questions that test students’ higher order thinking skills. The validation test of media, material, and learning experts received an average score of 82.81%, while the field trial on physics teachers received an average score of 84.73% and on students 91.01%. These scores show that the developed e-module is suitable for use as independent teaching materials for students. In addition, the calculation of the n-gain test is 0.48 and categorized as moderate according to the gain value interpretation table. This value shows that e-modules that present learning materials with videos, virtual laboratories, worksheets, and HOTS practice questions can improve students’ high-level thinking skills.